2011
DOI: 10.1002/pits.20577
|View full text |Cite
|
Sign up to set email alerts
|

Examining the validity of office discipline referrals as an indicator of student behavior problems

Abstract: Office discipline referral (ODR) data are increasingly used to monitor student behavior problems and the impact of interventions, but there has been limited research examining their validity. The current study examined the concordance of ODRs with teacher ratings of student behavior using data on 8,645 children in 335 classrooms at 21 elementary schools. The results of a variety of analyses (e.g., correlations, multivariate analysis of variance, receiver operating characteristics) suggested that ODRs are moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 28 publications
1
59
0
Order By: Relevance
“…Specifically, during the last month of the school year, the teachers completed a brief checklist in reference to each student in their classroom, on which they indicated whether the child had had been "sent to the principal's office" for disciplinary reasons during the current school year. Previous research from this project on this teacher-report variable in conjunction with administrative data from the School-wide Information System (SWIS; Irvin et al, 2004) regarding student-specific receipt of ODRs indicated that teacher reports are a valid and reliable source of information on ODRs (Pas et al, 2011). Specifically, Pas et al (2011) used a variety of methods, including ROC curves, to demonstrate an adequate level of sensitivity and specificity of the teacher-reported exclusionary discipline strategy; they also provided evidence of a moderate level of convergence between teacher-report and administrative (i.e., SWIS) data on the use of these practices.…”
Section: Classroom-level Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, during the last month of the school year, the teachers completed a brief checklist in reference to each student in their classroom, on which they indicated whether the child had had been "sent to the principal's office" for disciplinary reasons during the current school year. Previous research from this project on this teacher-report variable in conjunction with administrative data from the School-wide Information System (SWIS; Irvin et al, 2004) regarding student-specific receipt of ODRs indicated that teacher reports are a valid and reliable source of information on ODRs (Pas et al, 2011). Specifically, Pas et al (2011) used a variety of methods, including ROC curves, to demonstrate an adequate level of sensitivity and specificity of the teacher-reported exclusionary discipline strategy; they also provided evidence of a moderate level of convergence between teacher-report and administrative (i.e., SWIS) data on the use of these practices.…”
Section: Classroom-level Variablesmentioning
confidence: 99%
“…A common disciplinary strategy employed by teachers is the use of exclusionary discipline strategies, such as office discipline referrals (ODRs) or suspensions. ODRs are events in which a staff member observes a student violating a school rule and submits documentation to the administrative leadership, who then delivers a consequence (Irvin, Tobin, Sprague, Sugai, & Vincent, 2004;Pas, Bradshaw, & Mitchell, 2011). Exclusionary discipline strategies typically include the immediate removal of the student from the classroom, as the student is typically sent to the principal's office in an effort to try to stem the problem behavior.…”
Section: Classroom Contextual Influencesmentioning
confidence: 99%
“…Teachers can have set, preconceived notions and beliefs regarding the level of possible educational attainment for their African American students including their possible level of performance (Rosenthal and Jacobson 1968). For example, these biases can manifest as higher rates of school discipline for African American students (Pas, Bradshaw and Mitchell 2011), higher rates of diagnosed learning disorders for African American students (Skiba, Poloni-Staudinger, Simmons et al 2005), or other forms of discrimination towards the students (Mickelson 2003). Thus, although the current public school system that exists in American society is shaped around the theme that each student has equal opportunity and access to the same education, a prevalent gap still exists regarding the educational level students are able to achieve even within the same school (Begeny, Eckert, Montarello et al 2008, Clayton 2011, Halvorsen et al 2008, Michael-Luna and Marri 2010, Posey-Maddox 2014, Tyson 2011.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…The analysis presented in this section is not focused on whether there is a legitimate need for disciplinary actions, but rather on how disciplinary actions are handed out to the students. The disparities in discipline originate with the individuals who are able to refer students for disciplinary actions (Bates and Glick 2013, McIntosh et al 2015, Okonofua and Eberhardt 2015, Pas et al 2011. It is believed many of such individuals hold in their minds a preconceived concept regarding the identity of students who are likely to be disruptive and whose actions warrant disciplinary intervention.…”
Section: Disciplinary Differencesmentioning
confidence: 99%
See 1 more Smart Citation